Virtual Reality as a Context for Adaptation - Yarossi, Mathew; Mangalam, Madhur; Naufel, Stephanie; Tunik, Eugene (Frontiers in Virtual Reality, 2021)
The COVID-19 pandemic has accelerated interest in virtual reality (VR) for education, entertainment, telerehabilitation, and skills training. As the frequency and duration of VR engagement increases — the number of people in the United States using VR at least once per month is forecasted to exceed 95 million — it is critical to understand how VR engagement influences brain and behavior. Here, we evaluate neurophysiological effects of sensory conflicts induced by VR engagement and posit an intriguing hypothesis: the brain processes VR as a unique ‘context’ leading to the formation and maintenance of independent sensorimotor representations. We discuss known VR-induced sensorimotor adaptations to illustrate how VR might manifest as a context for learning and how technological and human factors might mediate the context-dependency of sensorimotor representations learned in VR.